Attachment to God as a source of struggle and strength : exploring the association between Christians' relationship with God and their emotional wellbeing - Calvert, Sarah Jenay (Massey University, 2010)
Research has highlighted the significant implications of spirituality for mental health and therapy. However, a key facet of spirituality yet to receive adequate research attention is people’s experience of their relationship with God. One useful theoretical framework recently applied to this relationship is attachment theory. Research suggests that many people experience their relationship with God as an attachment bond, and that styles of attachment to God (ATG) may have implications for mental health similar to human attachment. However, few studies have directly investigated the relationship between ATG and mental health, and limitations of these studies make it difficult to draw conclusions. The present study provides a more rigorous exploration of this relationship through the use of a cross-lagged research design, advanced statistical modelling, and investigation of potential moderators (gender and negative events). A convenience sample of 531 Christian adults was surveyed at two time points approximately four months apart. ATG was measured on two dimensions: ATG-avoidance (avoidance of intimacy with/dependence on God) and ATG-anxiety (preoccupations and fears regarding God’s rejection). Higher levels of baseline ATG-anxiety predicted poorer emotional wellbeing at Time 2, after controlling for baseline emotional wellbeing. This effect was stronger amongst participants experiencing a high level of negative events. Findings also indicate a potential mechanism for this effect. Specifically, ATG-anxiety was associated with a tendency to appraise negative events as indicating God’s abandonment/punishment. These appraisals mediated the relationship between ATG-anxiety and emotional wellbeing. In contrast, low levels of ATG-anxiety buffered the effects of negative events. The effects of ATG-anxiety were significant only amongst males, contrary to hypotheses. ATG-avoidance did not show hypothesised effects on emotional wellbeing in either gender. Possible limitations of the ATG-avoidance measure were noted, and may have influenced findings. Suggestions were made as to how future studies might address this potential measurement issue and other limitations of the study. Findings indicate that ATG theory may have useful therapeutic applications, as proposed by previous researchers. Specifically, the ATG framework may be useful for conceptualising clients’ relationship with God and its effects on mental health, although establishing this will ultimately require testing in clinical samples.
Keywords: Attachment to God; Emotional wellbeing; Christians; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology